2009
DOI: 10.1073/pnas.0900827106
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing the developmental pathways TTF-1 , NKX2–8 , and PAX9 in lung cancer

Abstract: We investigated the clinical implications of lung developmental transcription factors ( TTF-1 , NKX2–8 , and PAX9 ) that we recently discovered as cooperating oncogenes activated by way of gene amplification at chromosome 14q13 in lung cancer. Using stable transfectants of human bronchial epithelial cells, RNA expression profiles (signatures) representing activation of the biological pathways defined by each of the 3 genes were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 39 publications
1
35
1
1
Order By: Relevance
“…It is said that MAPKinase, JAK/STAT and Wnt are important in activation of TTF1 and NKX8, connected with EGFR and Her2. 46 The expression of cyclin D1 was higher in tumoral than in normal tissue and RB expression had no statistical difference when compared to normal tissue. This fact may indicate a tendency to proliferate, because once cyclin D1 is in high concentration, it could phosphorylate more RB protein and release E2F, involved in the regulation of genes with implications in cell cycle progression (G1 to S phase).…”
Section: Acinar Patternmentioning
confidence: 86%
“…It is said that MAPKinase, JAK/STAT and Wnt are important in activation of TTF1 and NKX8, connected with EGFR and Her2. 46 The expression of cyclin D1 was higher in tumoral than in normal tissue and RB expression had no statistical difference when compared to normal tissue. This fact may indicate a tendency to proliferate, because once cyclin D1 is in high concentration, it could phosphorylate more RB protein and release E2F, involved in the regulation of genes with implications in cell cycle progression (G1 to S phase).…”
Section: Acinar Patternmentioning
confidence: 86%
“…Nkx2-1, Nkx2-8 (Nkx homeobox-8 gene), and PAX9 (paired box gene 9), the three transcription factors known to mediate lung development and maturation, were recently characterized as cooperating oncogenes located together on chromosome 14q13 (Hsu et al, 2009). NSCLC patients with early stage tumors that expressed both Nkx2-1 and Nkx2-8 had poor survival.…”
Section: Role Of Nkx2-1 In Diagnosis Of Lung Cancermentioning
confidence: 99%
“…3). We also detected a significant increase in transcript levels for other pulmonary epithelial transcription factors in hESC-H9 progeny, including GATA6 and PAX9 [21,26,27], but not PAX8, expressed by thyroid epithelium [28,29]. Immunostaining demonstrated that > 80% of hESC-H9 progeny stained positive for FOXA2, of which approximately 6% co-stained with antibodies against NKX2-1 (Fig.…”
Section: Activin-a Induces Nkx2-1 Expressionmentioning
confidence: 69%